Polymeric Mesoporous Silica Nanoparticles for Enhanced Delivery of 5-Fluorouracil In Vitro - Thashini Moodley; Moganavelli Singh (MDPI AG, 2019)
There is a need for the improvement of conventional cancer treatment strategies by incorporation of targeted and non-invasive procedures aimed to reduce side-effects, drug resistance, and recurrent metastases. The anti-cancer drug, 5-fluorouracil (5-FU), is linked to a variety of induced-systemic toxicities due to its lack of specificity and potent administration regimens, necessitating the development of delivery vehicles that can enhance its therapeutic potential, while minimizing associated side-effects. Polymeric mesoporous silica nanoparticles (MSNs) have gained popularity as delivery vehicles due to their high loading capacities, biocompatibility, and good pharmacokinetics. MSNs produced in this study were functionalized with the biocompatible polymers, chitosan, and poly(ethylene)glycol to produce monodisperse NPs of 36−65 nm, with a large surface area of 710.36 m2/g, large pore volume, diameter spanning 9.8 nm, and a favorable zeta potential allowing for stability and enhanced uptake of 5-FU. Significant drug loading (0.15−0.18 mg5FU/mgmsn), controlled release profiles (15−65%) over 72 hours, and cell specific cytotoxicity in cancer cells (Caco-2, MCF-7, and HeLa) with reduced cell viability (≥50%) over the non-cancer (HEK293) cells were established. Overall, these 5FU-MSN formulations have been shown to be safe and effective delivery systems in vitro, with potential for in vivo applications.